Evaluation of the Effectiveness of Educational Resource Management in Reducing Discrimination - Nurlaily, Nurlaily; Agustina, Agustina; Pujiati, Sri (EDUCTUM: Journal Research, 2024)
Educational management is a relatively young discipline that combines management principles in an effort to improve the quality of education. The aim is to achieve effectiveness and efficiency in achieving educational goals through planning, organizing, giving orders, coordinating, controlling and evaluating. Even though various policies and programs have been implemented, the education system in Indonesia still has not shown adequate results in creating quality human resources. Therefore, it is necessary to further study existing problems and formulate alternative solutions to overcome existing weaknesses. Improving the quality of educational human resources requires good management in order to compete on a global scale. Evaluation is an important part of this process, providing information that can be used for decision making, policy formulation, and program improvement. Systematic and ongoing evaluation helps ensure that programs are implemented effectively and efficiently, and provides a strong basis for future policy development.